2019
DOI: 10.1038/s41379-018-0127-2
|View full text |Cite
|
Sign up to set email alerts
|

Well-differentiated papillary mesothelioma of the peritoneum is genetically defined by mutually exclusive mutations in TRAF7 and CDC42

Abstract: Well-differentiated papillary mesothelioma is an uncommon mesothelial neoplasm that most frequently arises in the peritoneal cavity of women of reproductive age. Whereas malignant mesothelioma is an aggressive tumor associated with poor outcome, well-differentiated papillary mesothelioma typically exhibits indolent behavior. However, histologically differentiating between these two entities can be challenging, necessitating the development of distinguishing biomarkers. While the genetic alterations that drive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 44 publications
6
67
2
1
Order By: Relevance
“…What is surprising in our results is the absence of the TRAF7 and CDC42 alterations reported by Yu et al [7] and Stevers et al [11] in WDPM and by the same group in adenomatoid tumors [29]. Alterations in TRAF7 have also been reported in malignant mesotheliomas [4,16,30].…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…What is surprising in our results is the absence of the TRAF7 and CDC42 alterations reported by Yu et al [7] and Stevers et al [11] in WDPM and by the same group in adenomatoid tumors [29]. Alterations in TRAF7 have also been reported in malignant mesotheliomas [4,16,30].…”
Section: Discussioncontrasting
confidence: 65%
“…Nevertheless, using immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH), Lee et al demonstrated that, unlike in malignant mesothelioma, both BAP1 and CDKN2A are intact and respective proteins are expressed in WDPMs [10]. More recently, Stevers et al [11] performed genomic profiling of 10 WDPMs and found that they harbored TRAF7 or CDC42 mutually exclusive missense mutations.…”
Section: Introductionmentioning
confidence: 99%
“…TRAF7, a member in the tumor necrosis factor (TNF) receptor-associated factor family, is an E3-ubiquitin ligase in the NF-kB signaling pathway to regulate diverse processes such as transcription, survival, and cytokine production. Recurrent mutations in TRAF7 are present in a subset of meningiomas [32][33][34], intraneural perineuriomas [35], well-differentiated papillary mesotheliomas [36,37], most adenomatoid tumors of the genital type [38,39], and rare cases of diffuse malignant pleural mesothelioma [7]. The two TRAF7 mutations p.S561R and p.Q613E in localized pleural mesotheliomas are located in one of the seven Cterminal WD40 domain repeats.…”
Section: Discussionmentioning
confidence: 99%
“…Copy-number loss of BAP1, CDKN2A/B, LAST1/2, and NF2 is frequently found in pleural mesothelioma 4,5 . 11 What is surprising in our results is the absence of the TRAF7 and CDC42 alterations reported by Yu et al 7 and Stevers et al 11 in WDPM and by the same group in adenomatoid tumors 31 . Alterations in TRAF7 has also been reported in malignant mesotheliomas 4,20,32…”
Section: Discussionmentioning
confidence: 48%